The Spatial Characteristics of Hourly Rainfall Induced by Tropical Cyclones Along the South China Coast. Issue 11 (1st November 2021) - Ali, Riaz; Li, Qinglan; Chen, Ji; Huang, Dian; Lu, Xiaoxiong
Abstract: Accurate prediction of tropical cyclone (TC) induced rainfall is of great importance to disaster prevention but quite challenging to operational forecasters. This study quantifies the spatial characteristics of the hourly rainfall caused by TCs at several individual weather stations over the south China coast. We use the historical TC datasets from 2004 to 2018 and the hourly rainfall data from six weather stations to investigate the stations' rainfall distribution characteristics induced by TCs within a distance of 700 km to the weather stations. The hourly rainfall data during the study period from six coastal stations: Zhuzilin (ZZL), Shekou Ferry Terminal (SFT), and Wutong Village (WTV) in Shenzhen, and Hong Kong Observatory (HKO), Sha Tin (SHA), and Tai Mo Shan (TMS) in Hong Kong are used to investigate the statistical relationship. Results show that the most hazardous areas for TC‐induced rainfall are TCs within a distance of 200 km relative to the stations. High intensity TCs in the southwest quadrant may bring torrential rainfall to stations within 500 km distance, and low intensity TCs are likely to induce torrential rainfall to stations within 300 km distance when they are in the northeast and northwest quadrants. If TCs are over the region with the azimuth of 60–150° and distance out of 200 km to the six stations, there is almost no rainfall influence on those stations. The findings of this study are valuable to provide information for the local operational forecasters when predicting the potential rainfall along the south China coast due to future TCs. Key Points: The most hazardous areas for tropical cyclones (TCs) induced rainfall are TCs within a distance of 200 km to the station TCs are more likely to bring torrential rainfall to a coastal station when they are in the southwest quadrant of the station TCs have almost no impact on rainfall when the azimuth is between 60 and 150° and distance is out of 200 km from the station